Smučanje za mlajše otroke - Videmšek, Dušan (Šport (Ljubljana), 2018)
A game is the key method used to teach children how to ski. Many of the games can be carried out directly on the snow, and through them children, motivated by fun, learn the basic elements of skiing. Spearing the children of unnecessary guidance, we let their creativity flow. It is crucial for a child to show interest in skiing, while teaching should be gradual and adjusted to his or her developmental stage.
Keywords: igra; otroci; smučanje; smučarska oprema; učenje; vadba; zimski športi